Factors associated with knowledge of pre-exposure prophylaxis in pregnant women in Cape Town, South Africa. (October 2019) - DiTullio, David J; Farley, Elise; Gomba, Yolanda; Coates, Thomas J.; Bekker, Linda-Gail; Myer, Landon; Joseph Davey, Dvora L.
Pregnant and postpartum women in Southern Africa are at increased risk of HIV infection. Pre-exposure prophylaxis in pregnancy and postpartum periods could significantly reduce the risk of HIV acquisition and transmission in pregnancy. Participants at a community health clinic in Cape Town completed a survey about demographic and sexual risk behaviors, and prior knowledge of pre-exposure prophylaxis. We evaluated factors associated with knowledge of pre-exposure prophylaxis using multivariable logistic regression. We enrolled 50 pregnant and 37 postpartum women, of whom 51% were HIV-uninfected. Twenty-nine (33%) knew about pre-exposure prophylaxis, most from their healthcare provider (69%). Older age (adjusted odds ratio [aOR]/year = 1.09, 95% CI = 1.00–1.19), unintended pregnancy (aOR = 3.36, 95% CI = 1.06–12.12), and more than one sex partner in the last year (aOR = 5.31, 95% CI = 1.12–30.07) were associated with pre-exposure prophylaxis knowledge. Our study identified low levels of pre-exposure prophylaxis knowledge in pregnant and breastfeeding women, but increased knowledge in higher risk women. These results provide guidance to develop interventions to increase pre-exposure prophylaxis knowledge and uptake.